2020
DOI: 10.3390/molecules25020398
|View full text |Cite
|
Sign up to set email alerts
|

γ-Tocotrienol and α-Tocopherol Ether Acetate Enhance Docetaxel Activity in Drug-Resistant Prostate Cancer Cells

Abstract: Prostate cancer is the second most commonly diagnosed cancer in men, and metastatic prostate cancer is currently incurable. Prostate cancer frequently becomes resistant to standard of care treatments, and the administration of chemotherapeutic drugs is often accompanied by toxic side effects. Combination therapy is one tool that can be used to combat therapeutic resistance and drug toxicity. Vitamin E (VE) compounds and analogs have been proposed as potential non-toxic chemotherapeutics. Here we modeled combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…132 The best combination treatment was identified as gamma-tocotrienol with alpha-tocopherol ether acetate and docetaxel that could evade drug resistance in prostate cancer treatment than docetaxel given alone. 132 The synergistic action of gamma-tocotrienol and polysaccharopeptide (PSP) has been investigated in which, prostate cancer cell growth, proliferation, and cytotoxicity were seen to reduce, through the mediation of AMPK. 133 The researchers of this study had observed an increase in AMPK with the simultaneous inactivation of acetyl-co A carboxylase, an integral step in cellular energy homeostasis, evidenced by the Ser 79-activated phosphorylation.…”
Section: Chemo-sensitization By Tocotrienolmentioning
confidence: 99%
“…132 The best combination treatment was identified as gamma-tocotrienol with alpha-tocopherol ether acetate and docetaxel that could evade drug resistance in prostate cancer treatment than docetaxel given alone. 132 The synergistic action of gamma-tocotrienol and polysaccharopeptide (PSP) has been investigated in which, prostate cancer cell growth, proliferation, and cytotoxicity were seen to reduce, through the mediation of AMPK. 133 The researchers of this study had observed an increase in AMPK with the simultaneous inactivation of acetyl-co A carboxylase, an integral step in cellular energy homeostasis, evidenced by the Ser 79-activated phosphorylation.…”
Section: Chemo-sensitization By Tocotrienolmentioning
confidence: 99%
“…Since berberine and wogonin were found in combination so often in the optimal treatments and reduced cells up to greater than 50%, we further tested a MDRSM combination on a docetaxel‐ resistant PC3 cell line. Previously in our lab, we grew the DR‐PC3 cell line to demonstrate chemotherapy resistant cells 6 . We treated the DR‐PC3 cell line with a three‐way combination of shikonin, berberine, and wogonin.…”
Section: Resultsmentioning
confidence: 99%
“…This problem is more likely to occur with the compounds that have a stepwise shape to their IC50 curve (Figure 1). Perhaps choosing a higher drug concentration for the 100% treatments, that is points 1–3 in Figure 2A, would ensure the concentrations used at the subsequent mixture points, points 4–10 in Figure 2A, are biologically relevant for subsequent studies, as used by Asay et al Furthermore, the MDRSM model can be improved by adding additional points to augment the simplex model and improve the fit and allow for a more exact predicted optimal treatment 6 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations